2004
DOI: 10.1097/00005537-200401000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Results With Titanium Ossicular Reconstruction Prostheses

Abstract: Newer titanium-based ossicular reconstruction devices represent an improvement over previously used non-titanium-based prostheses. The authors think that this improvement is realized rapidly because no learning curve existed in their data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
85
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 19 publications
19
85
2
1
Order By: Relevance
“…Extrusion rates in our study were comparable to those of Ho et al [13] (4%) and of Begall et al [10] (4.4%). Rates of revision surgery were higher compared to other studies by Stupp et al [11] (5.6%), Martin and Harner [15] (7%) and Gardner et al [14] (6%).…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Extrusion rates in our study were comparable to those of Ho et al [13] (4%) and of Begall et al [10] (4.4%). Rates of revision surgery were higher compared to other studies by Stupp et al [11] (5.6%), Martin and Harner [15] (7%) and Gardner et al [14] (6%).…”
Section: Discussioncontrasting
confidence: 59%
“…A study done by Stupp et al [11,12] found a success rate of 76%, studies by Ho et al [13] and Gardner et al [14] have reported success rate of 56% (64% for PORP and 45% for TORP) and 71% for PORP and 44% for TORP respectively. In the present study success was considered after attaining dry ear and with a postoperative improvement of an Air Bone Gap of 20 dB or less and our success rate was 76.47% (75% for PORP and 77.77% for TORP).…”
Section: Discussionmentioning
confidence: 96%
“…One or all of these factors can have implications in the use of ossicular prostheses, extrusions and middle ear sound conduction. Similar hearing outcomes have been observed in other studies on type 3 ossicular reconstruction using titanium prostheses [16,20,21].…”
Section: Comparison With Other Studiessupporting
confidence: 89%
“…Nowadays, in some ear specialists' opinion, long-term follow-ups may even reach up to 20% of extrusion-related failures. Recently, both hydroxylapatite (HA), due to its chemical similarity to the mineral phase of the osseous tissue (Grote et al 1981;Grote 1986;Wehrs 1995;Goldenberg and Driver 2000;Rondini-Gilli et al 2003) and, more recently, titanium (Ti) (Stupp et al 1999;Zenner et al 2001;Ho et al 2003;Gardner et al 2004;Martin and Harner 2004), due to its processability in minute shape and its success as bone substitute, are the most commonly used biomaterials for ossicular prostheses.…”
Section: Introductionmentioning
confidence: 99%